Analisis Penggunaan Afiks pada Legenda Laowemaru dalam Cerita Rakyat Karya FG. Harefa - Giawa, Prilian; Gulo, Necis Putra; Giawa, Yarniwati; Harefa, Noveri Amal Jaya (Lembaga Intelektual Muda (LIM) Maluku, 2024)
This research aims to find out the types of affixes found in the legend of laowemaru in folklore by F.G Harefa. A type of qualitative research with a descriptive approach. The collection technique uses reading and note-taking techniques. The instruments used consisted of books, notes/worksheets, and pens by reading early, marking, and recording/pouring the results on the worksheet. The data analysis techniques used include data reduction, data presentation, and conclusion drawing. The results of the research show that there are several types of affixes found in the legend of Laowemaru in the folklore by F.G Harefa, including (1) prefixes including mo-, me-, la-, fa- and I-, (2) the infix -ga-, (3) the suffix -nia, and (4) the confix la-I.